Effect of Wallpass Exercise With Groups Of 4 Improving Passing Results Bali United Mataram - Soemardiawan, Soemardiawan; Nurdin, Nurdin (Universitas Suryakancana, 2021)
Football is a sport that is played outside the room of 11 players with the aim of getting the ball into the opponent's goal. The results of observations in the field that there are still many players in passing while competing so that it is not in accordance with the target. The formulation of the problem in this study is whether there is an effect of wallpass training and exercise with groups of 4 to increase the passing results of Bali United Mataram. The purpose of this research is to find out. The research design was a twogroup pretest-postest design. Population and sample are all players totaling 22 people. Instrument Passing for 30 seconds. The research data were analyzed using SPSS version 22. The results of the t-test for group 1 obtained significant values (2-tailed) <0.05: 0.003 <0.05 and group 2 significant values (2-tailed) <0.05: 0.038 <0,05. So these results indicate a significant difference. Based on the test for the difference in the mean post-test data for groups 1 and 2, it was obtained a significant value (2-tailed) <0.05: 0.026 <0.05 with an increase in the percentage value in group 1 of 12.93% and group 2 of 3, 96%. Based on the results of the analysis, it can be concluded that the effect of wallpass training and exercise with groups of 4 is an increase in the passing results of Bali United Mataram in 2021.Keywords: Passing, Wallpass, with groups of 4